Project Upward mantle flow from novel seismic observations (UPFLOW): DEPAS ocean-bottom seismometer operations in the North Atlantic in 2021-2022 - Ana M G Ferreira (PANGAEA, 2025)
The goal of the UPFLOW project is to develop new high-resolution seismic imaging approaches along with new data collection, and to use them to constrain upward flow in unprecedented detail. We conducted a large off-shore experiment in the Azores-Madeira-Canary Islands region, which is a unique natural laboratory with multiple upwellings that are poorly understood in general. UPFLOW deployed and recovered 49 ocean bottom seismometers (OBSs) in a ~1,000 exttimes2,000 km2 area in the Azores-Madeira-Canary Islands region starting in July 2021 for ~13 months, with an average spacing of ~150-200 km. The seismic deployment and recovery involved institutions from five different countries: Portugal (IPMA, IDL, Univ. of Lisbon, ISEL), Ireland (DIAS), UK (UCL), Spain (ROA) and Germany (Potsdam University, GFZ, Geomar, AWI). 32 OBSs were rented from the DEPAS international pool of instruments maintained by the Alfred Wegener Institute (Bremerhaven), Germany, while other institutions borrowed additional instruments (7 from DIAS, 4 from IDL, 3 from ROA, 4 from GEOMAR). Most of the instruments have three-component wideband seismic sensors, but three different designs of OBS frames were used. Waveform data is available from the GEOFON data centre, under network code 8J, embargoed data may be accessible upon request. Raw data from DEPAS OBS are archived here. We want to acknowledge the exceptional support of the whole team of able seaman, steward, cooks, engineers, mechanicians, electricians and motorman assistants of the vessel RRV Mário Ruivo. The following persons contributed to the data set: Miguel Miranda; Sameneh Baranbooei; Roberto Cabieces Diaz; Carlos Corela; José Luis Duarte; Henrique Ferreira; Wolfram H. Geissler; Katrina Harris; Stephen Hicks; Kasra Hosseini; Kuan-Yu Ke; Frank Krueger; Dietrich Lange; Afonso Loureiro; Peter Makus; Augustin Marignier; Marta Neres; Luis Ramos; Theresa Rein; Alex Saoulis; David Schlaphorst; Frederik Tilmann; Maria Tsekhmistrenko; José Ângelo Gomes (Captain), Luís Ramos (Superintendent), Mafalda Carapuço Vessel extquotesingles manager (IPMA), Henrique Ferreira Land logistics (IPMA), Celine Ahmed and Jen Amery (Administrative support at UCL) .